Выявление интонационных особенностей музыкального произведения на примере анализа фортепианной миниатюры АЛЕКСАНДРА СПЕНДИАРЯНА - Юрьевна Ваганян, Наира (Musical Armenia, 2011)
The theoretical analytical article “Detection of intonation specifics of music works by the example A. Spendiaryan’s piano miniature’s analysis” of aspirants of Kh. Abovyan Armenian State Pedagogical University Naira Yu. Vahanyan rrepresents music as a intonation art. The display of intonational features in a piece music (on the example of the analysis of a piano miniature). The present article presents music as a piece of intonational (tone) art. Each piece of music has its intonation, which is the reflection of the composer's musical thought and emotions. The article presents an intonational and rhythmical analysis of the "Men's Dance" piano version from the opera "Almast" by Alexander Spendiaryan. It aims at devising new methods and approaches for a more expressive piano intoning of a piece of music.